Oxidative stress induces senescence in human mesenchymal stem cells - Brandl, Anita; Meyer, Matthias; Bechmann, Volker; Nerlich, Michael; Angele, Peter (Experimental cell research, 2011)
Mesenchymal stem cells (MSCs) contribute to tissue repair in vivo and form an attractive cell source for tissue engineering. Their regenerative potential is impaired by cellular senescence. The effects of oxidative stress on MSCs are still unknown. Our studies were to investigate into the proliferation potential, cytological features and the telomere linked stress response system of MSCs, subject to acute or prolonged oxidant challenge with hydrogen peroxide. Telomere length was measured using the telomere restriction fragment assay, gene expression was determined by rtPCR. Sub-lethal doses of oxidative stress reduced proliferation rates and induced senescent-morphological features and senescence-associated β-galactosidase positivity. Prolonged low dose treatment with hydrogen peroxide had no effects on cell proliferation or morphology. Sub-lethal and prolonged low doses of oxidative stress considerably accelerated telomere attrition. Following acute oxidant insult p21 was up-regulated prior to returning to initial levels. TRF1 was significantly reduced, TRF2 showed a slight up-regulation. SIRT1 and XRCC5 were up-regulated after oxidant insult and expression levels increased in aging cells. Compared to fibroblasts and chondrocytes, MSCs showed an increased tolerance to oxidative stress regarding proliferation, telomere biology and gene expression with an impaired stress tolerance in aged cells.